Overview of Model Free Adaptive (MFA) Control Technology - Al Smadi Takialddin; Osman Ibrahim Al-Agha; Khalid Adnan Alsmadi (IAES International Journal of Artificial Intelligence (IJ-AI), 2018)
Model-Free Adaptive (MFA) control is a technology that has made a major impact on the automatic control industry. MFA control users have successfully solved many industry-wide control problems in various applications and achieved significant economic benefits. Now, the challenge is extending the many advantages of MFA control technology to diverse and fragmented markets, which could benefit from its unique capabilities. Since single-loop MFA controllers can directly replace legacy PID controllers without the need for "system" redesign (plugand play), they are readily embeddable in various instruments, equipment, and smart control valves. This alleviates concerns relative to cost of change and also makes MFA an appealing tool for OEM applications on a large scale.